Shear modified Lemaitre damage model for fracture prediction during incremental sheet forming. (1st October 2022) - Kumar, Abhishek; Kumar Singh, Abhishek; Shrivastava, Amber; Mishra, Sushil; Narasimhan, K
Highlights: A shear modified Lemaitre damage model implemented for incremental sheet forming (ISF). Maximum deformable wall angle & fracture depth predictions compare well with experiments. At higher wall angle, plastic strain & stress triaxiality increase fast, triggering damage. Deformation during ISF is under mixed mode between plane strain and biaxial stretching. Abstract: The incremental sheet forming process is an emerging manufacturing process with high process flexibility, higher formability and inexpensive tooling. Previous experimental and numerical studies have proposed various hypotheses for the deformation mechanisms during incremental sheet forming. Further, studies suggest that the formability in incremental sheet forming is limited by the fracture. This makes it important to predict the fracture and stress state induced during the incremental sheet forming process. The present work is focused on the implementation of shear modified Lemaitre damage model with a finite element method to predict the damage/fracture during incremental sheet forming of truncated cones. The Lemaitre model parameters were estimated from the loading–unloading test and calibrated against the tensile, notched tensile and shear test experiments. Various truncated cones were formed incrementally at different wall angles, till a fracture appeared on the cone surface. Similarly, several simulations of incremental sheet forming with different wall angles were performed to predict the fracture. The analysis of stress triaxiality and Lode angle parameter shows the mixed-mode (plane stress and biaxial stretching) of deformation during the incremental sheet forming process. The predicted fracture depth shows an error of 4.36% with the experimental results. It is concluded that the shear modified Lemaitre model predicts the fracture cone wall angle and depth during incremental sheet forming with good accuracy.